Report on alternaria blight of Tagetes erecta and Tagetes patula caused by Alternaria alternata (Fr.) Keissler (Journal of the Asiatic Society of Bangladesh, Science, 2014)
Severe blight symptom was recorded on Tagetes erecta L. and Tagetes patula L. during the tenure of January to April 2009, 2010, 2011, 2012 and 2013. Samples were collected from Chittagong, Comilla, Dhaka, Gazipur, Khulna, Pabna, Rajshahi and Sylhet. Fungi associated with infected samples were isolated following Tissue Planting and Blotter methods at temperature 25-280C and pH 6.0. Alternaria alternata (Fr.) Keissler was isolated from diseased leaves, buds, calyx and petals of both selected plant species. The pathogenicity of the isolated fungus was tested following modified detached leaf technique and spraying of spore suspension methods. Alternaria alternata was found to be pathogenic to Tagetes spp. This is the first report on Alternaria blight of T. erecta and T. patula from Bangladesh.J. Asiat. Soc. Bangladesh, Sci. 40(1): 133-140, June 2014